Kebijakan Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK) dalam Penelusuran Aset Pelaku Tindak Pidana Korupsi - Agnes Permata Sari, Eko Soponyono, R.B. Sularto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
PPATK is an independent department which has directly responsibility ti President RI as defined in the regulation of money laundering. The existence of PPATK as an intelligence department that has a main function in provide and deliver financial intelligence to law enforcement officer in terms of the alleged money laundering or predicate offenses (in this case of corruption). Corruption is an regulation of confiscation of assets that belongs to the states so the state loses its ability to carry out the duties and responsibilities for the welfare of society. Policy conducted by PPATK regarded as a breakthrough to find the right of the assets at the time of this offense. Asset tracking in result of corruption cases should be reform by looking at the rise of the case that occurred during this period. The policy pursued PPATK expected to provide maximum results in reducing cases of corruption.